(untitled) (Quinto Sol, 2025)
This article addresses the life of the Tucumán Foundation within the context of the reorganization, rise, and crisis of local liberalism in the recent past. To accomplish this task, its public interventions, editorial research and dissemination endeavors, and the collection of oral sources were analyzed. Furthermore, the organization’s political life was placed in dialogue with global, national, and local actors with a view to reconstructing its multi-scale networks. In this way, it was possible to analyze the circulation and reception of liberal ideology at a local level, the unique aspects of its critique of the state form, and its ties with the government of the province of Tucumán.